(untitled) (Research, Society and Development, 2022)
Introduction: Edentulism can occur due to several precedents, such as caries, periodontal disease and trauma, having a great influence on quality of life, both biologically and psychologically. The objective of this literature review was to address the forms of oral rehabilitation in edentulous people, the psychosocial factors and the effects caused by it on aesthetics. Methodology: Literature review, with a descriptive approach. Results: The impact generated by it in these patients is found in speech, appearance, chewing and occlusal functioning, which negatively interfere with self-esteem. Results and discussions: The advancement of dentistry in oral rehabilitation is currently present to reduce and solve these problems, thus making it more possible with rehabilitation treatments such as partial dentures, removable prostheses, fixed partial dentures and dental implants. Promoting efficacy both in occlusion and aesthetics, improving the oral and systemic cavity of patients. Conclusion: Edentulism influences the patient psychosocially, causing a pejorative impact after tooth loss and thus decreasing their quality of life, both physical and functional.